Evaluation of the efficiency of a vertical flow constructed wetland combined with a coconut fiber filter for pork slaughterhouse wastewater treatment - Ho, Lien Bich; Nguyen, Tuyet Anh Huynh; Huynh, An The (Brawijaya University, 2025)
Water pollution is considered a concerning issue in both Vietnam and the world. The cause contributing to water pollution is the impact of animal slaughter activities. Slaughterhouses discharge a large amount of untreated wastewater into the surrounding environment, causing significant degradation of the water environment as well as human health problems. Therefore, it is necessary to treat wastewater from slaughterhouses before discharging it into water sources. The objectives of the study were to determine the quality of wastewater from pork slaughterhouses in Binh Duong and evaluate the effectiveness of a vertical flow constructed wetland combined with a coconut fiber filter for treating this wastewater through the parameters of pH, suspended solid (SS), biology oxygen demand (BOD), chemical oxygen demand (COD), colors, total nitrogen (TN), total phosphorus (TP), and total coliform. The constructed wetland was made of gravel and sand with vertical flow. Vetiver grass (Vetiveria zizanioides (Linn) Nash) was used as the macrophyte. The results showed that, except for pH, all other parameters surveyed from the pork slaughterhouses exceeded the standards QCVN 40:2011/BTNMT (column B). It was observed that increasing the retention time of treatment in the constructed wetland caused an increase in the removal efficiency. The maximum removal efficiency of the treatment system for the parameters SS, BOD5, COD, colors, TN, TP, and total coliform was 96,21%, 83,21%, 89,53%, 95,70%, 81,99%, 97,72%, and 99,99%, respectively. It can be concluded that the combination of a constructed wetland and a coconut fiber filter performed well for the treatment of slaughterhouse wastewater.